Condicionamientos sintácticos en la desaparición del infinitivo en griego antiguo - Nieto Ibáñez, Jesús María (1995)
En su evolución al griego medieval y moderno todo el sistema verbal griego experimenta una transformación muy profunda y marcada. Como es bien sabido, de los modos personales desaparece el optativo y de los no personales el infinitivo, mientras que el participio es sustituido por un gerundio indeclinable. Por otra parte, dentro de los temas verbales han surgido nuevas formas perifrásticas sustitutivas de los antiguos futuros y perfectos.
In the koiné the syntax of the infinitive shows a series of differences as regards classical standars (on the one hand the replacement of the infinitive by conjunctive constructions and verbal personal forms, and on the other, its reinforcement by means or articles, conjunctions and other particles) which anticipate its later complete disappearance. However, the main reason for this loss of stabilization in the infinitive does not seem to be the typical phonetic change th at takes place at this stage of the language, but its own syntax, that is, the infinitive as the neuter term, the unmarked element of those syntactic oppositions in which it is found.
Keywords: Sintaxis; Infinitivo